Penerapan Kaidah Istishab sebagai Dasar Penetapan Keabsahan Akad dalam Transaksi Keuangan Syariah Kontemporer - Iib Hibaturohman; Asep Risnandar; Syahrul Anwar; Ending Solehudin; Tb Rifat (CV. Global Cendekia Inti, 2026)
The rapid growth of Islamic financial transactions in Indonesia has given rise to various new products and contracts that require a solid legal foundation in Islamic law that is scientifically sound. One of the principles of usul al-fiqh that is highly relevant but has not yet been studied in depth in the context of the modern Islamic economy is the principle of istishab. This study aims to analyze the position of the Istishab principle within the hierarchy of Islamic legal evidence, examine its application as the basis for determining the validity of contracts in contemporary Islamic financial transactions, and formulate its implications for Islamic financial regulations in Indonesia. This study employs a normative legal research method using usul al-fiqh, conceptual, and comparative approaches. Primary data sources include the Qur’an, Hadith, classical and contemporary usul al-fiqh texts, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and regulations from the Financial Services Authority (OJK). The results of the study indicate that the principle of Istishab, through the principles of al-yaqinu la yuzalu bi al-syakk and al-ashlu fi al-asya' al-ibahah, possesses legal force that can serve as a basis for determining the validity of Islamic financial contracts, particularly in situations of legal uncertainty arising from the emergence of new financial products. The application of istishab has been found to be relevant to financing contracts (murabahah and mudharabah), investment contracts (sukuk and Sharia-compliant mutual funds), and technology-based transactions within the Sharia fintech ecosystem.